IVUS-guided evaluation and percutaneous intervention in an anomalous left main coronary artery. - Schrale, R; Channon, K; Ormerod, O (2007)
We report the case of a 42-year-old female with proven anterior ischemia and an anomalous origin of the left main coronary artery (ALMCA) who underwent successful percutaneous coronary intervention (PCI) with intravascular ultrasound (IVUS) guidance. Angiographic and IVUS images demonstrate features unique to the ALMCA. The epidemiology, pathophysiology, evaluation and management options, including technical considerations for percutaneous intervention, are discussed. The ALMCA from the right sinus of Valsalva represents one of the few potentially serious congenital coronary artery anomalies. These patients are often young, have atypical presentation and carry a risk of sudden death. In combination with unfamiliar anatomy and pathophysiology, they pose serious diagnostic and therapeutic challenges. We present our experience in a patient who underwent successful PCI with IVUS guidance, and discuss the anatomy, pathophysiology, evaluation and treatment options for the ALMCA.